Potencial acción fitofarmacológica de Porophyllum ruderale, una fuente natural de compuestos polifenólicos - Ramos, Norma J. (2024)
Medicinal plants are becoming more important every day as alternatives to various diseases compared to chemical therapies. The present bibliographic review aims to identify the phytochemical characteristics of the phenolic compounds and phytopharmacological activities of Porophyllum ruderale, responsible for its nutritional properties and its anti-inflammatory, antileshmanial and antioxidant activity, for this we describe some phytochemical characteristics of Porophyllum ruderale that could be responsible of its medicinal properties. Despite there being limited scientific information on all the mechanisms of action and medicinal activities of Porophyllum ruderale, this review brings together a series of studies that report its anti-inflammatory, antileshmanial and antioxidant activity. In this way, through the bibliographic review, important information was collected on the phytochemical characteristics of the phenolic compounds that demonstrate phytopharmacological activities of Porophyllum ruderale, as well as nutritional properties and anti-inflammatory, antileshmanial and antioxidant activity. Thus, encouraging future researchers to carry out experimental studies that contribute to the health care of the population.